Rethinking AI Acceptance in Corporate: A Human-Centric Extension of UTAUT - Alasmari, Talal (Journal of Ecohumanism, 2024)
In the business corporate world, artificial intelligence (AI) is becoming a disruptive force. This study explores the intricacies of adopting AI in corporate environments, emphasizing factors that affect both behavioral intentions and real usage patterns. This study, which drew on the Unified Theory of Acceptance and Use of Technology (UTAUT), identified the distinctive features of AI and added new determinants, including perceived humanness, bias, job threat, functionality, transparency, and privacy and security issues. These determinants cover technological, human-centric, and situational aspects which can either catalyze or hinder AI acceptance. Our quantitative research, involving 223 professionals across diverse sectors in Saudi Arabia, expanded the UTAUT model by revealing critical factors driving AI acceptance, including ethics and privacy considerations. Intriguingly, certain latent factors were identified to inversely affect AI application. This research addresses important ethical, security, and operational issues related to AI deployment, while also expanding the theoretical understanding of AI’s role in business. Such insights are paramount for decision-makers, practitioners, and academics alike, ensuring the sustainable and responsible incorporation of AI in the business realm.